2018
DOI: 10.1042/bcj20180475
|View full text |Cite
|
Sign up to set email alerts
|

Isoform-specific AMPK association with TBC1D1 is reduced by a mutation associated with severe obesity

Abstract: AMP-activated protein kinase (AMPK) is a key regulator of cellular and systemic energy homeostasis which achieves this through the phosphorylation of a myriad of downstream targets. One target is TBC1D1 a Rab-GTPase-activating protein that regulates glucose uptake in muscle cells by integrating insulin signalling with that promoted by muscle contraction. Ser237 in TBC1D1 is a target for phosphorylation by AMPK, an event which may be important in regulating glucose uptake. Here, we show AMPK heterotrimers conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 71 publications
(81 reference statements)
0
18
3
Order By: Relevance
“…The R125W coding variant in TBC1D1 has been linked to an increased risk for familial obesity in humans (5,6). Modeling studies based on related PTB domain structures suggested that the R125W exchange might affect certain ligand binding properties of the first PTB domain in TBC1D1 and AMPK interaction (35,36). However, in this study we found no evidence that addition of excess PTB domains alters the GAP activity of TBC1D1 in vitro.…”
Section: Regulation Of Recombinant Tbc1d1 In Vitrocontrasting
confidence: 78%
“…The R125W coding variant in TBC1D1 has been linked to an increased risk for familial obesity in humans (5,6). Modeling studies based on related PTB domain structures suggested that the R125W exchange might affect certain ligand binding properties of the first PTB domain in TBC1D1 and AMPK interaction (35,36). However, in this study we found no evidence that addition of excess PTB domains alters the GAP activity of TBC1D1 in vitro.…”
Section: Regulation Of Recombinant Tbc1d1 In Vitrocontrasting
confidence: 78%
“…This could involve an inhibition of endocytosis as observed in cardiomyocytes, as this would allow a slow build-up of cell-surface GLUT4 even when exocytosis occurs at the slow basal rate. Studies on phosphorylation of signalling intermediates, such as TBC1D1 and TBC1D4, suggest signalling convergence of insulin and AMPK signalling [ 80 , 86 ], but the kinetics of GLUT4 translocation suggest signalling from insulin and AMPK can have divergent effects on GLUT4 traffic. Changes in the AMP/ATP ratio that result from stimulation of the ‘exercise’ signalling pathway may have effects on endocytosis that are not present following an insulin treatment and are possibly independent of TBC1D1 and TBC1D4.…”
Section: Use Of Biotinylated Glut Photolabelsmentioning
confidence: 99%
“…We and others have previously demonstrated that the PTB domains of TBC1D1 bind to 14-3-3 proteins 33,[36][37][38] , IRAP 30,33,35 , AMPK complexes containing α1 but not α2 catalytic subunits 33 and APPL2 65 . Using a differentiated in vitro muscle cell model and intact mouse quadriceps muscle, we extend this repertoire of validated binding proteins to include VPS13A, VPS13C, EHBP1L1, MICAL1 and SERCA1.…”
Section: Discussionmentioning
confidence: 89%
“…Mouse model. Transgenic MCK-3xFLAG-Tbc1d1 mice with muscle-specific overexpression of Tbc1d1 were generated as previously described 33 and kept in accordance with the National Institutes of Health guidelines for the care and use of laboratory animals, and all experiments were approved by the Ethics Committee of the State Ministry of Agriculture, Nutrition and Forestry (State of North Rhine-Westphalia, Germany). Male mice between 10 and 14 weeks were sacrificed by cervical dislocation, quadricep muscle dissected and directly snap-frozen in liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation